Development of Digital Comics Integrated with Pancasila Student Profiles in The Merdeka Curriculum to Enhance Narrative Text Comprehension - Naisa'ada, Rika; Mulyani, Petra Kristi (LPPM Universitas Pendidikan Mandalika, 2025)
This study investigates the development, feasibility, and effectiveness of Nafi Lala (Narasi Profil Pelajar Pancasila), a digital comic designed to enhance fourth-grade students' reading comprehension of narrative texts through the integration of Pancasila Student Profile dimensions in the Merdeka Curriculum. The research employs a research and development method, utilizing the ADDIE model, and collects data through interviews, questionnaires, pretests, posttests, and documentation. The study involves a small group of six students and a large group of 19 fourth-grade students in Semarang City, Central Java. Both qualitative and quantitative data analysis methods are applied, with qualitative data analyzed based on expert feedback and quantitative analysis involving normality tests, paired sample t-tests, and N-Gain analysis. The results show that the teaching module and content receive a score of 90%, while the media component achieves 92%, both categorized as